Olefin Metathesis Under Continuous Flow Mode - Skowerski, Krzysztof; Wierzbicka, Celina; Grela, Karol (Current Organic Chemistry, 2013)
This mini-review describes approaches to conduct olefin metathesis catalysed by transition metal catalysts in continuous flow (CF) mode. In this context extremely high efficiency of well defined Mo and Ru catalysts is highlighted.
Keywords: Molybdenum